Effects of an imagery workshop on coaches' encouragement of imagery use - Edwards, J.; Law, B.; Lamer-Cheung, A. (International Journal of Sports Science and Coaching, 2012)
The purpose of this study was to examine whether an imagery workshop would increase recreational level coaches' encouragement of imagery to their athletes when compared to coaches attending a communication workshop. The workshops provided coaches with information, teaching tools, as well as role-playing opportunities. Recreational sport coaches (n = 132; M age = 41.80 years, SD = 9.67) completed the Coaches Encouragement of Athletes Imagery Use Questionnaire (CEAIUQ), Coach-Athlete Relationship Questionnaire (CART-Q), and questionnaires assessing coaches' confidence, knowledge, and attitudes towards imagery. Repeated measure MANCOVAs, controlling for sex and highest level coached, revealed no group by time interactions for any of the five functions of imagery. However, group by time interactions were found for knowledge, attitudes and confidence towards imagery. The imagery group significantly increased their confidence from baseline to follow-up (t(65) = -2.75, p = .01). Findings provide direction for designing future coach education training programs and aid in understanding recreational sport coaches' views on encouraging their athletes to use imagery.